Perineální hernie - plastika pomocí laloku přímého břišního svalu - Bocková, M; Hoch, J; Frajer, L (Rozhledy v chirurgii, 2016)
UNLABELLED: Perineal hernia is defined as a protrusion of intra-abdominal viscera through a defect in the pelvic floor. Primary hernias are extremely rare; secondary (postoperative) hernias following pelvic surgery, especially abdominoperineal resection or pelvic exenteration, are more common. Impaired perineal wound healing and neoadjuvant chemoradiotherapy in cancer patients are defined as main risk factors. A growing incidence of this complication is expected in connection with an increasing use of laparoscopic approaches and ELAPE. Despite the considerable time since the first described secondary perineal hernia in literature, patient series, prospective studies and treatment guidelines are still missing. The authors present a case of a 66-year-old man with secondary perineal hernia following a previous laparoscopic abdominoperineal resection for rectal cancer undergoing a surgical intervention. This was performed through an abdominal approach using a rectus abdominis muscle flap to repair the pelvic floor defect. KEY WORDS: perineal hernia - hedrocele - RAM - abdominoperineal resection.
Keywords: Perineum; musculus rectus abdominis; Magnetic Resonance Imaging; magnetická rezonanční tomografie; Humans; Herniorrhaphy; laparoskopie; Aged; pánevní dno; senioři; lidé; perineum; Incisional Hernia; Rectus Abdominis; nádory rekta; Surgical Flaps; Pelvic Floor; Rectal Neoplasms; Male; operace kýly; chirurgické laloky; Laparoscopy; incizní kýla; mužské pohlaví; prospektivní studie; Prospective Studies